Changing Management of the Patent Ductus Arteriosus: Effect on Neonatal Outcomes and Resource Utilization - Chock, Valerie Y.; Goel, Veena V.; Palma, Jonathan P.; Luh, Thomas M.; Wang, Nichole A.; Gaskari, Shabnam; Punn, Rajesh; Silverman, Norman H.; Benitz, William E. (American Journal of Perinatology, 2017)
Objective This historical cohort study investigated how a shift toward a more conservative approach of awaiting spontaneous closure of the patent ductus arteriosus (PDA) in preterm infants has affected neonatal outcomes and resource utilization.Methods We retrospectively studied very low birth weight infants diagnosed with a PDA by echocardiogram (ECHO) in 2006–2008 (era 1), when medical or surgical PDA management was emphasized, to those born in 2010–2012 (era 2) when conservative PDA management was encouraged. Multiple regression analyses adjusted for gestational age were performed to assess differences in clinical outcomes and resource utilization between eras.Results More infants in era 2 (35/89, 39%) compared with era 1 (22/120, 18%) had conservative PDA management (p < 0.01). Despite no difference in surgical ligation rate, infants in era 2 had ligation later (median 24 vs. 8 days, p < 0.0001). There was no difference in clinical outcomes between eras, while number of ECHOs per patient was the only resource measure that increased in era 2 (median 3 vs. 2 ECHOs, p = 0.003).Conclusion In an era of more conservative PDA management, no increase in adverse clinical outcomes or significant change in resource utilization was found. Conservative PDA management may be a safe alternative for preterm infants.
Keywords: patent ductus arteriosus; conservative management; preterm infant; outcomes; resource utilization; historical cohort